2019
DOI: 10.3390/md17120661
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genomics and CAZyme Genome Repertoires of Marine Zobellia amurskyensis KMM 3526T and Zobellia laminariae KMM 3676T

Abstract: We obtained two novel draft genomes of type Zobellia strains with estimated genome sizes of 5.14 Mb for Z. amurskyensis KMM 3526Т and 5.16 Mb for Z. laminariae KMM 3676Т. Comparative genomic analysis has been carried out between obtained and known genomes of Zobellia representatives. The pan-genome of Zobellia genus is composed of 4853 orthologous clusters and the core genome was estimated at 2963 clusters. The genus CAZome was represented by 775 GHs classified into 62 families, 297 GTs of 16 families, 100 PLs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 69 publications
(57 reference statements)
2
18
0
Order By: Relevance
“…Strain 62-1 furthermore encodes PL33 and PL40 lyases that potentially target ulvan (Table 1). CAZyme numbers and diversity match the hydrolytic potential of related Maribacter and Zobellia strains included for comparison ( Supplementary Table S1), corroborating the adaptation of these taxa to algal substrates and surfaces (Bakunina et al 2012, Martin et al 2015, Kwak et al 2017, Zhan et al 2017, Chernysheva et al 2019.…”
Section: Cazymes In the Phylogenomic Contextsupporting
confidence: 68%
“…Strain 62-1 furthermore encodes PL33 and PL40 lyases that potentially target ulvan (Table 1). CAZyme numbers and diversity match the hydrolytic potential of related Maribacter and Zobellia strains included for comparison ( Supplementary Table S1), corroborating the adaptation of these taxa to algal substrates and surfaces (Bakunina et al 2012, Martin et al 2015, Kwak et al 2017, Zhan et al 2017, Chernysheva et al 2019.…”
Section: Cazymes In the Phylogenomic Contextsupporting
confidence: 68%
“…Of a total of 233 CAZymes encoded in the ING2-E5A T genome, 154 GHs account for 44 different families ( Figure 3 ). Previous studies on Gram-negative bacteria of the phylum Bacteroidetes also reported on a large variety of different GH families in these species (up to 62) [ 64 ]. Based on these observations, a broad biodegradation potential regarding carbohydrates is proposed for this phylum.…”
Section: Resultsmentioning
confidence: 99%
“…The PS06 genome harbored various genes involved in carbohydrate metabolism, including genes encoding carbohydrate-active enzymes (CAZymes). The identified CAZymes provide insight into their lifestyles and potential applications in biomedicine or biotechnology [ 72 , 73 ]. CAZymes have been classified by following modules: glycoside hydrolases (GHs), glycosyltransferases (GTs), polysaccharide lyases (PLs), carbohydrate esterases (CEs), auxiliary activities (AAs), and carbohydrate-binding modules (CBMs).…”
Section: Resultsmentioning
confidence: 99%
“…CAZymes have been classified by following modules: glycoside hydrolases (GHs), glycosyltransferases (GTs), polysaccharide lyases (PLs), carbohydrate esterases (CEs), auxiliary activities (AAs), and carbohydrate-binding modules (CBMs). Also, bacterial CAZymes have been characterized for synthesis and degradation of polysaccharides as a rich source of bioactive compounds in algae including seaweeds and recognized as an eco-friendly enzyme for improving the yield and quality for derivatives of algal polysaccharides [ 73 , 74 ]. Although a number of marine heterotrophic bacteria are involved in the degradation of various biopolymers including, polysaccharide degradation, little is known about the gene repertories of hydrolytic systems in the genus Thalassotalea .…”
Section: Resultsmentioning
confidence: 99%